Hubungan antara Tingkat Keteraturan Kontrol dengan Tingkat Ketaatan Pengobatan pada Penderita Gangguan Psikotik Fase Awal di Yogyakarta - , RENATA ULI AVIOLA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Approximately 3% of people will experience a psychotic episode. First-episode occurs in adolescence or early adult life, crucial time for self development. Lack of understanding of psychotic leads to delay in seeking help besides this first-episode impact long-term outcome of the disease. Treatment for psychotic disorder is a challenging task. Complex psychosocial problem cause imperfect recovery. Patient with psychotic disorder is a major risk group for medication non-adherencee. Therefore preventive approach should be implemented, for example using clinical appointment regularity treatment may be useful. Objective: To identify the relationship between adherence with clinical appointment and medication adherence on patient with first-episode psychotic in Yogyakarta. Method: Cross-sectional data analysis between the period of October 2010 and March 2011. A number of 100 test subjects from RSUP Dr. Sardjito, RSJ Gharasia, RSK Puri Nirmala, RSUD Wates, RSUD Bantul and RSUD Gunungkidul were gathered. Adherence with clinical appointment and medication adherence were reported by caregiver in medication adherence form. Then statistical analysis were done using coefficient contingency. Result: There were 77,8% medication non-adherence subject which were also not adherence with clinical appointment, then 66,6% medication non-adherence subject, not adherence with clinical appointment regularly. Statistical result indicated p-value =0,000 and CC=0,841. Conclusion: There is a significant relationship between adherence with clinical appointment and medication compliance in patient with first-episode psychotic with the correlationâs degree is very strong.